2013
DOI: 10.1159/000343651
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Liver Injury Associated with Noni (Morinda citrifolia) Juice and Phenobarbital

Abstract: Noni (Morinda citrifolia) juice is a popular herbal dietary supplement globally used for preventive or therapeutic purposes in a variety of ailments, claiming to exhibit hepatoprotective properties as well. Herein we present the case of a 38-year-old woman who developed acute liver injury associated with noni juice consumption on a long-term (9 months) anticonvulsant therapy. Clinical presentation and liver biopsy were consistent with severe, predominantly hepatocellular type of injury. Both agents were stoppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Goji berry, the fruit of Lycium barbarum L., has been recently involved in hepatitis too (Franco et al 2012;Arroyo-Martinez et al 2011). Finally, many reports of suspected liver injuries from noni (Morinda citrifolia L.) are reported (Waldman et al 2013;Yu et al 2011;Stadlbauer et al 2008;López-Cepero Andrada et al 2007;Yuce et al 2006;Stadlbauer et al 2005;Millonig et al 2005), even if hepatotoxicity of noni juice remains speculative (Mrzljak et al 2013;West and Deng 2011). In this scenario, which component of Euforia ® induced liver injury remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Goji berry, the fruit of Lycium barbarum L., has been recently involved in hepatitis too (Franco et al 2012;Arroyo-Martinez et al 2011). Finally, many reports of suspected liver injuries from noni (Morinda citrifolia L.) are reported (Waldman et al 2013;Yu et al 2011;Stadlbauer et al 2008;López-Cepero Andrada et al 2007;Yuce et al 2006;Stadlbauer et al 2005;Millonig et al 2005), even if hepatotoxicity of noni juice remains speculative (Mrzljak et al 2013;West and Deng 2011). In this scenario, which component of Euforia ® induced liver injury remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, drug-induced hepatotoxicity is continuously emerging as a significant cause of liver disorders, representing today a leading cause of acute liver failure in economically developed countries (Mrzljak et al, 2013). During DOX therapy, the liver receives, accumulates and metabolizes high concentrations of DOX.…”
Section: Pretreatment Hepatoprotective Effect Of Regular Aerobic Traimentioning
confidence: 99%
“…Phenolic acids are consistently associated with reduced risk of cardiovascular disease, cancer and other chronic diseases by mechanisms related to the scavenging of free radicals and as prooxidant metals (antioxidant), although there are reports for toxic effects of compounds isolated from the fruit of M. citrifolia (Ee et al, 2009;Nualsanit et al, 2012;Aziz et al, 2014). Earlier reports indicated that fruits (Millonig et al, 2005;Stadlbauer et al, 2005; Yüce (West et al, 2006;Lopez-Cepero et al, 2007) and juice (Sivagnanam et al, 2011;Mrzljak et al, 2013) of M. citrifolia are hepatotoxic in humans, since preparations for them are rich inanthraquinones and coumarins (scopoletin) (Ee et al, 2009), they induce generation of free radicals derived from oxygen and trigger oxidative stress. Free radicals cause depletion of intracellular reduced glutathione and mitochondrial membrane potential, thus initiating lipid peroxidation and eventually, cell death (Su et al, 2005;Bussmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%